Diastereoselective Construction of CF3‐Containing Bispiro[isoquinolone‐pyrrolidine‐benzothiophenone]s through 1,3‐Dipolar Cycloaddition - Niu, Cheng; Du, Da‐Ming (European journal of organic chemistry, 2022)
A new protocol to access CF3‐containing bispiro[isoquinolone‐pyrrolidine‐benzothiophenone]s was described. A series of 1,3‐dipoles were synthesized from isoquinolinetrione and CF3CH2NH2. In the presence of 10 mol% DABCO, the 1,3‐dipolar cycloaddition of isoquinolinedione trifluoroethyl ketimines and unsaturated benzothiophenones delivered corresponding adducts in excellent yields (up to 98 %) and diastereoselectivities (up to >20 : 1 dr). An efficient and mild method to access CF3‐containing bispiro[isoquinolone‐pyrrolidine‐benzothiophenone]s is reported.